The impact of impaired semantic knowledge on spontaneous iconic gesture production - Cocks, Naomi; Dipper, L.; Pritchard, M.; Morgan, G. (Psychology Press (Taylor & Francis Group), 2013)
Background: Previous research has found that people with aphasia produce more spontaneous iconic gesture than control participants, especially during word-finding difficulties. There is some evidence that impaired semantic knowledge impacts on the diversity of gestural handshapes, as well as the frequency of gesture production. However, no previous research has explored how impaired semantic knowledge impacts on the frequency and type of iconic gestures produced during fluent speech compared with those produced during word-finding difficulties. Aims: To explore the impact of impaired semantic knowledge on the frequency and type of iconic gestures produced during fluent speech and those produced during word-finding difficulties. Methods & Procedures: A group of 29 participants with aphasia and 29 control participants were video recorded describing a cartoon they had just watched. All iconic gestures were tagged and coded as either “manner”, “path only”, “shape outline” or “other”. These gestures were then separated into either those occurring during fluent speech or those occurring during a word-finding difficulty. The relationships between semantic knowledge and gesture frequency and form were then investigated in the two different conditions.Outcomes & Results: As expected, the participants with aphasia produced a higher frequency of iconic gestures than the control participants, but when the iconic gestures produced during word-finding difficulties were removed from the analysis, the frequency of iconic gesture was not significantly different between the groups. While there was not a significant relationship between the frequency of iconic gestures produced during fluent speech and semantic knowledge, there was a significant positive correlation between semantic knowledge and the proportion of word-finding difficulties that contained gesture. There was also a significant positive correlation between the speakers’ semantic knowledge and the proportion of gestures that were produced during fluent speech that were classified as “manner”. Finally while not significant, there was a positive trend between semantic knowledge of objects and the production of “shape outline” gestures during word-finding difficulties for objects. Conclusions: The results indicate that impaired semantic knowledge in aphasia impacts on both the iconic gestures produced during fluent speech and those produced during word-finding difficulties but in different ways. These results shed new light on the relationship between impaired language and iconic co-speech gesture production and also suggest that analysis of iconic gesture may be a useful addition to clinical assessment.